Role of entrepreneurial orientation, social capital and government support policies in influencing Ghanaian SMEs performance - Zaato, Solomon Gbene (2022)
The performance of small and medium-sized enterprises (SMEs) is a growing concern since they are the largest contributor to a nation's Gross Domestic Product (GDP). In recent years, SMEs contribution towards reducing youth unemployment in Ghana has been on the decline due to low level of entrepreneurial orientation, social capital, and limited government support policies, resulting in high failure rate. Evidence also suggests little research on how entrepreneurial orientation influences Ghanaian SMEs performance. As a result, the goal of this research is to explore how other related variables like entrepreneurial orientation (EO-going forward), social capital and government support policies may influence SMEs performance in Ghana. Through a random sampling technique, data was obtained from 372 SME-owners in the services and manufacturing sectors of Ghana and was analysed using the Partial Least Square-Structural Equation Modelling (PLS-SEM) approach. The findings are that proactiveness, innovativeness, competitive aggressiveness, and autonomy all had positive and significant influence on SMEs performance except risk-taking, which although had positive outcome but it is not significant. The result also shows that social capital significantly influenced the performance of SMEs. Furthermore, proactiveness, innovativeness, and competitive aggressiveness had significant links with social capital except risk-taking and autonomy. Results on the mediation effect of social capital revealed positive and substantial intervening effects of proactiveness, innovativeness, and competitiveness, while risk-taking and autonomy were insignificant. More so, the findings signify that government support policies only had a significant interaction effect on the relationship between competitive aggressiveness and SMEs performance, with no moderating effect on the link between social capital and SMEs performance. The results also revealed that government support policies have a considerable influence on SMEs’ performance in Ghana. More notably, this study expanded the existing theories and used the model of strategic entrepreneurship, organizational learning, and learning organisation while underscoring the need for Ghanaian SMEs to have a competitive advantage to reduce their rate of insolvency and create more jobs and wealth. In accordance with the study findings, Ghanaian SMEs should embrace EO, expand their social capital networks, and become more proactive and competitive in order to gain access to government support policies and stay in business. Finally, with the provision of this empirical evidence, the current study adds to the existing literature on entrepreneurship and strategic management where implications for practice and recommendations for future study are thoroughly discussed.